PENDAMPINGAN PERBAIKAN LANTAI KERAMIK UPAYA PENINGKATAN KEAMANAN DAN KENYAMAN PROSES PEMBELAJARAN MI HUDALIL MUTTAQIEN KEDUNGPANAS: PENDAMPINGAN PERBAIKAN LANTAI KERAMIK UPAYA PENINGKATAN KEAMANAN DAN KENYAMAN PROSES PEMBELAJARAN MI HUDALIL MUTTAQIEN KEDUNGPANAS - Pangesti, Rendy Dwi; Kusumastuti, Dianita Ratna; Sulistiawati, Baiq Heny; Abdillah, Rifqi Aulia (Politeknik Negeri Semarang, 2025)
The quality of education is not only determined by the curriculum and teaching methods, but is also influenced by the physical condition of the learning environment, including the comfort and safety of the classroom. MI Hudalil Muttaqien Kedungpanas is one of the elementary schools that deals with problems with physical facilities, especially damaged ceramic floors in several classrooms. This damage has an impact on disrupting the teaching and learning process, and has the potential to pose a safety risk to students and teachers. This community service program aims to improve the quality of learning facilities by repairing damaged ceramic floors. The method of implementing the activity includes a survey of initial conditions, preparation of technical plans, Procurement of materials, to the repair process which is carried out in stages in accordance with civil engineering principles. The results of the community service that have been carried out show that floor repairs have succeeded in creating a more comfortable, safe, and suitable classroom environment for learning activities. In addition to improving aesthetics and safety, these repairs also have a positive impact on student learning motivation. This community service activity confirms that adequate physical facilities are an important factor in creating a quality educational environment and supporting an optimal learning process.